2004
DOI: 10.1242/jcs.01209
|View full text |Cite
|
Sign up to set email alerts
|

Glycine, GABA and their transporters in pancreatic islets of Langerhans: evidence for a paracrine transmitter interplay

Abstract: To elucidate the possible roles of the CNS neurotransmitters glycine and GABA in neuroendocrine paracrine signalling, we investigated their localizations, and those of their transport proteins, by confocal immunofluorescence and quantitative post-embedding immuno-electron microscopy in the pancreatic islets of Langerhans. We show that A-cells contain glycine in synaptic-like microvesicles as well as in secretory granules. A-cells express the macromolecules necessary to: (1) concentrate glycine within both orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 52 publications
3
69
0
2
Order By: Relevance
“…Moreover, the neuronal transmitters GABA and glycine, and their vesicular transporters, are essential for paracrine transmitter interplay in the pancreas [27]. All these findings strongly support the 'conscious cell' concept proposed by Lynn Margulis -that all eukaryotic cells are able to use neuronal principles for controlling their complex behavior in the face of the huge amount of information that cells continuously receive, store and process for making adaptive decisions about their further states and activities [28].…”
Section: Neuronal Molecules In Plantssupporting
confidence: 60%
“…Moreover, the neuronal transmitters GABA and glycine, and their vesicular transporters, are essential for paracrine transmitter interplay in the pancreas [27]. All these findings strongly support the 'conscious cell' concept proposed by Lynn Margulis -that all eukaryotic cells are able to use neuronal principles for controlling their complex behavior in the face of the huge amount of information that cells continuously receive, store and process for making adaptive decisions about their further states and activities [28].…”
Section: Neuronal Molecules In Plantssupporting
confidence: 60%
“…Unexpectedly, VIAAT was found to localize to the glucagon-containing secretory granules rather than to the synaptic-like microvesicles also present in islet cells. In contrast, Gammelsaeter et al (2004) identified VIAAT in both secretory granules and microvesicles in rat islet cells and also detected comparatively low levels in the cells.…”
Section: Introductionmentioning
confidence: 72%
“…In the islets, it probably also functions as an intercellular signaling molecule, perhaps -as there is evidence to suggest -as a paracrine or autocrine regulator of insulin or glucagon secretion (Chessler & Lernmark 2000, Braun et al 2004a. Recent evidence suggests that a second inhibitory neurotransmitter, glycine, also plays a role in islet function (Gammelsaeter et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry and immunogold electron microscopy show that rat b-cells express the vesicular amino acid transporter (VIAAT/VGAT), which mediates glycine uptake into synaptic vesicles in neurons and accumulates glycine in secretory granules (30). These findings, and the ability of strychnine to inhibit insulin secretion from human islets (above), suggest that b-cells may release glycine by exocytosis to mediate autocrine signaling.…”
Section: Glycine Release From Human B-cellsmentioning
confidence: 94%